Methods for using worker-centered research to improve food donation and reduce wasted food in a grocery retail setting - Harper, Kaitlyn; Espat, Steffanie; Davis, Lee; Labruto, Nicole; Neff, Roni A. (Frontiers in Public Health, 2025)
IntroductionThis project took a novel approach to reducing wasted food and improving food donation by prioritizing and centering the ideas and experiences of frontline grocery retail workers, who were integrally involved in each step of the research process. In this paper, we describe in detail the methods used in the Food Donation Champions Project, a worker-centered project in collaboration with a large US grocery retail chain. We provide the context, process, and lessons learned through our partnership with corporate leaders and frontline workers.MethodsThis project was conducted using a convergent, human-centered design process, involving design, public health, and anthropology research methodologies. The process involved six steps: planning, research, synthesis, ideation, prototype development and testing, and strategy finalization. We collected qualitative data through interviews and observations with grocery retail workers, members of corporate leadership, and stores' donation partners (i.e., food pantries and food banks). Frontline workers informed this research strategy and participated in all stages of analysis and strategy development.DiscussionThe process and findings described in this paper provide researchers and leaders in grocery retail a guide to a novel methodology and research approach that may be used to enhance projects that elevate the lived experience of people most central to addressing social and environmental problems.